(untitled) (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2019)
One indicator to measure the success of public organizations that provide services to the community is community satisfaction. Of course the problems that arise can be seen from the complaints felt by the recipient community. The purpose of this study was to find out: the index of community satisfaction with public services at the Cirebon Regency Population and Civil Registry Service and the factors that influence the level of community satisfaction at Disdukcapil Cirebon District. The type of research used is descriptive research, a study conducted to obtain a description/description of the implementation of service. Keywords: Public Service, Satisfaction Index, Disdukcapil